Taxonomic novelties in Calydorea Herbert (Iridaceae): Tigridieae) II - Deble, Leonardo Paz; Rodriguez, Janaina Bonfada; Oliveira-Deble, Anabela Silveira de; Filipini, Tatiana Gonçalves de Lima (Balduinia, 2014)
A new species, named Calydorea charruana is described, illustrated and has its taxonomic affinities discussed. The new species is closely related to C. azurea but differs by its connate style branches, shape and length of stem bract. The new species easily differs from Calydorea nuda because of its bigger flowers that open during early morning and wither around midday. Moreover, a collection of Calydorea nuda is reported from Aceguá municipality, Rio Grande do Sul State, resulting in the inclusion of this species to the Brazilian flora.